GROWTH PERFORMANCE OF BROILERS UNDER TWO REARING SYSTEMS IN THREE DIFFERENT HOUSING ZONES IN AN ENVIRONMENTALLY CONTROLLED HOUSE DURING WINTER - K. Bilal; S. Mehmood; M. Akram; S. Imran; A.W. Sahota; K. Javed; J. Hussain; H. Ashfaq (Journal of Animal and Plant Sciences, 2014)
An experiment was conducted with the intent to compare the growth performance of broilers housed under two different rearing systems (cage and floor) placed in three housing zones (near vent, middle and near variable speed fans). For this purpose, a total of 240 day old commercial broilers (Hubbard Classic) were reared on floor and cages divided into three above mentioned housing zones. Each treatment was replicated four times containing 10 birds apiece. Weekly data on feed intake, body weight gain, FCR and production efficiency factor (PEF) were recorded and analyzed using Analysis of Variance (ANOVA) technique in Completely Randomized Design (CRD) under factorial arrangements and means were compared through Duncan’s Multiple Range Test (DMR). Results revealed that significantly (P<0.05) better body weight (2098.25±73.88 g) feed intake (3901.13±134.01 g), PEF (263.34±9.71) and FCR (1.90±0.00) on floor than those reared on the cages. The body weight (2266.81±53.4g) feed intake (4218.50±94.98 g), PEF (284.76±7.16) FCR (1.90±0.00) were found to be best near vents followed by middle and fan area. It may be concluded that birds reared on floor placed near the vent area exhibited better growth performance as compared to those reared in cages in other housing zones.
Keywords: broiler; rearing system; growth performance; housing zones